(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
From the changing the concept of family, the paper analyses the Italian legal framework on Medically Assisted Reproduction (MAR) after the Constitutional Court ruling n. 162/2014, that eliminated the ban on heterologous in vitro fertilization. The author, through the analysis of the different laws under a comparative perspective, points out the necessity of detailed rules applicable with particular reference to the right of the newborn to know his/her family background, the issues relating to donors, and the implementation problems at regional level.